Tai-sabaki and the body position in Seoi-nage - Ishii, T.; Kanamaru, Y.; Ae, M.; Okada, H.; Komata, K. (Association for the Scientific Studies on Judo, Kodokan, 2011)
The purpose of this study is to clarify the biomechanical characteristics of Tai-sabaki and the body position at the end of Tai-sabaki in Seoi-nage. We recruited five elite judo athletes for the study. We measured the linear distance between the right ankle and the left ankle, the stance width-height ratio, the duration of the leg swing, the knee flexion angle and the trunk inclination angle.